PATRIOTIC TOURISM DEMAND IN ALBANIA: A SYSTEM GMM MODEL APPROACH (The South East European Journal of Economics and Business, 2023)
This paper aims to evaluate the determinants of international tourism demand in Albania following the existing literature and particulars of the tourism sector in Albania using Dynamic Panel Data from 2011 to 2019. The analysis is conducted on the sample of 20 countries of origin using the Two-Step GMM Model. The analysis highlights the importance of word-of-mouth effect in the tourism industry in Albania marked at the same time by inferior goods and services, as defined by the microeconomic theory. While on the one hand, tourism becomes very useful in terms of social cohesion (converging familiars and relatives), on the other hand, it can support better the general economic development. At the same time, this study underlines the relative importance of Government Spending. The National strategy on tourism must look not only at the tourism demand quantity but mostly at the sustainable and greater added value tourism segments.